2014
DOI: 10.21273/hortsci.49.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Efficient In Vitro Screening for Higher Soil pH Adaptability of Intersectional Hybrids in Blueberry

Abstract: We tested efficient in vitro methods for screening the genotypes with higher pH tolerance using multiple shoots of intersectional hybrids between Vaccinium corymbosum ‘Spartan’ and V. bracteatum. The response of the four hybrid clones tested to different pH levels was clone-dependent in vitro. An apparent difference was found in the rooting rate among the hybrid clones even at higher pH levels; the rooting rates of JM4 (91%) at pH 8.0 indicated a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Our results suggest that using NO 3 for blueberry fertilization might lead to rhizosphere alkalization. In blueberry, high rhizosphere pH can lead to nutrient deficiencies, stunted growth, and low survival (Finn et al, 1993;Tsuda et al, 2014). Thus, NO 3 use would exacerbate the need for soil amendments and soilless substrates for blueberry cultivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that using NO 3 for blueberry fertilization might lead to rhizosphere alkalization. In blueberry, high rhizosphere pH can lead to nutrient deficiencies, stunted growth, and low survival (Finn et al, 1993;Tsuda et al, 2014). Thus, NO 3 use would exacerbate the need for soil amendments and soilless substrates for blueberry cultivation.…”
Section: Resultsmentioning
confidence: 99%
“…Plants in family Ericaceae (i.e., acid-loving plants) thrive in acidic soils (pH 4.2-5.5) where NH 4 + is the most abundant form of N (Marrs and Bannister, 1978). When acid-loving plants are grown in neutral or high-pH soils, they exhibit stress, nutritional deficiencies, stunted growth, and low survival (Finn et al, 1993;Marrs and Bannister, 1978;Paya-Milans et al, 2017;Tsuda et al, 2014). Acidic soils are rare in agricultural and landscape settings.…”
mentioning
confidence: 99%
“…Different blueberry species and cultivars usually have different resistances to high pH levels. Tsuda et al [10] found that the interspecific hybrids of highbush blueberry 'Spartan' and V. bracteatum had higher survival and rooting rates than their parents, of the 'Spartan' variety, did, at a pH level of 8.0; moreover, there were significant differences among the different hybrids. Finn et al [4,9] found that the survival or germination rates and biomasses of different highbush blueberries, lowbush blueberries, and their hybrid offspring were different under high pH conditions, and the resistance of some lowbush blueberry offspring could be improved through a hybrid method.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding blueberry cultivars with a high pH tolerance is one of the appropriate ways to solve this problem. Different species and cultivars of Vaccinium have different abilities to tolerate high pH values [4,9,10], so new cultivars of blueberry with more tolerance to high-pH soil can be bred through a breeding program. However, new blueberry germplasms created by crossing or other breeding methods usually take several years to bloom and bear fruit.…”
Section: Introductionmentioning
confidence: 99%
“…It also possesses tolerance to higher pH soils. Tsuda et al (2013) using a colchicine-doubled species selection [ 30 ], produced 66 4 x hybrids and some hybrids were shown to have pigmented flesh a subsequent manuscript Tsuda et al (2014) documented the superior rooting of several hybrids at higher pH levels [ 31 ]. Vaccinium meridionale Swartz is a tetraploid native to Jamaica and Colombia.…”
Section: Breeding Beyond the Primary Genepool For Blueberrymentioning
confidence: 99%